Microwave-assisted extraction of lipid and eicosapentaenoic acid from the microalga Nanochloropsis sp. using imidazolium-based ionic liquids as an additive in water - Motlagh, Shiva Rezaei; Khezri, Ramin; Etesami, Mohammad; Chee, Ching Yern; Kheawhom, Soorathep; Nootong, Kasidit; Harun, Razif (Springer Science and Business Media, 2024)
This study employed 1-ethyl-3-methyl imidazolium chloride ([EMIM][Cl]) as an additive in an aqueous medium, combined with microwave-assisted extraction (IL-MAE), to extract total lipids and eicosapentaenoic acid (EPA) from the microalga Nannochloropsis sp. microalgae. The optimization process involved evaluating critical operating parameters, including the type of extraction solvent, solid-loading (i.e., water: microalgae ratio), extraction time, extraction temperature, and the IL/biomass ratio on the extraction of total lipids and as well as its EPA content. Under optimal conditions, IL-MAE significantly enhanced total lipid yield and EPA content by approximately 2.72 times and 8.1 times, respectively, compared to the traditional Soxhlet extraction. The standard Soxhlet procedure resulted in approximately 6.20% total lipids and 4.61 mg g-1 of EPA. Notably, with IL-MAE, the highest lipid and EPA yields were achieved. These reached 16.87% and 37.28 mg g-1, respectively, under optimal conditions: 90 °C for 25 min, using 2 w/w IL/biomass ratio, with 0.5 g of algae and a 3.3% w/v solid-loading. The obtained FAMEs through transesterification of total lipids exhibited high quality, comprising 37.94% wt polyunsaturated fatty acids (PUFAs). SEM and FTIR confirmed IL-MAE's superior lipid extraction by disrupting glycosidic linkages in the microalgal cell wall, resulting in a significantly higher yield than Soxhlet extraction. Repeated use of recycled [EMIM][Cl], tested up to four times, did not impact lipid and fatty acids recovery. Cost evaluation revealed that the IL-MAE approach for lipid production from Nannochloropsis sp. is more cost-efficient than the Soxhlet method, considering biomass, chemical and energy consumption. The enhanced extraction performance and accelerated rates of the IL-MAE system demonstrate its efficacy in extracting lipids, EPAs, and PUFAs from microalgae. Furthermore, it emphasizes sustainable, green, and efficient approach for extracting bioactive compounds, offering potential applications in the pharmaceutical and nutraceutical industries. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.